The chronologers' quest: Episodes in the search for the age of the earth - Jackson, Patrick Wyse (Cambridge University, 2013)
The debate over the age of the Earth has been ongoing for over two thousand years, and has pitted physicists and astronomers against biologists, religious philosophers against geologists. The Chronologers' Quest tells the story of our attempts to determine the age of the Earth. This book investigates the many novel methods used in the search for the Earth's age, from James Ussher and John Lightfoot examining biblical chronologies, Comte de Buffon and Lord Kelvin determining the length of time for the cooling of the Earth, to the more recent investigations of Arthur Holmes and Clair Patterson into radioactive dating of rocks and meteorites.